Time series modelling and forecasting of Sarawak black pepper prices / Liew Khim Sen, Mahendran Shitan and Huzaimi Hussain - Liew, Khim Sen; Shitan, Mahendran; Huzaimi, Hussain (Universiti Teknologi MARA, Sarawak, 2003)
Pepper is an important agriculture commodity especially for the state of Sarawak. It is important to forecast its price, as this can help the policy makers in coming up with production and marketing plans to improve the Sarawak's economy as well as the farmers' welfare. In this paper, the time series models are used to forecast the Sarawak black pepper price. It is formally shown in this paper that the pepper price series does not follow a random shows that Autoregressive Moving Average (ARMA) time series models fit the price series well. The ARMA (1,0) model seems to be the best fitting model predicting the pepper price based on the data used in this study.